The impact of living conditions and organizational practices as brain drain cause factors on the human resource assets of the health sector in the Gaza strip – Palestine - Sami Ali Abou-AL-Ross (Research, Enlightment, Findings Accelerated Applications Development ( REFAAD), 2021)
This study aims at identifying the impact of some of the cause factors of brain drain, particularly, living conditions and organizational practices, on the human resource assets of the health sector in the Gaza Strip, clarifying the role of those factors in increasing the brain drain phenomenon and what influence it has over the human resource assets. The descriptive analytical approach was adopted. In addition, a questionnaire was designed to collect data from physicians from the health sector using random sample. The conclusions indicated that both living conditions and organizational practices were rated by the respondents as having negative influence as brain drain cause factors. In addition, it negatively influenced the human resource asset. Moreover, there is a significant positive relationship between brain drain cause factors (living conditions and organizational practices) and human resource assets. This means improvements in the factors causing brain drain will lead to the same in the status of human resource assets. Accordingly, it is recommended to emphasize fairness, equity, equality, and anti-discrimination policies. Furthermore, continuously review and develop advanced organizational systems, such as career advancement, promotions, salary scales, incentives and rewards, in addition to appreciation and acknowledgment of competent employees. Moreover, there is a focus on investing in human resource assets through applying professional human resource practices related to human resource planning, and training and development.